Hydraulic performance of berm breakwaters - Jensen, O.J. (author); Sorensen, T. (author) (ASCE, 1989)
Rubble mOlJnd breakwaters have been used for centuries for the protection of harbours. In many cases breakwaters were built in relatively deep water and exposed to waves too severe in relation to the size of rock used for construction. Furthermore, they were often built with a steep slope, and consequently, severe damage occurred. In some cases, breakwaters have been repaired by a continuous supply of stones until an almost stable equilibrium slope developed. In this way, the breakwaters at Cherbourg, Plymouth and Holyhead, Refs. /2/ & /3/ were developed. At certain places in nature the same may be observed for gravel beaches, where the available material by wave and tidal action is reshaped until an almost equilibrium situation occurs. In recent years, the concept of unconventional rubble mound breakwaters, i.e. berm breakwaters, has gained much attention among researchers and engineers as an economical method to build breakwaters at certain sites. At DHI, the principle of berm breakwaters was first used in 1978 for the Skopun Breakwater Extension, Faroe Islands . Berm Breakwaters